2014
DOI: 10.1016/j.bcp.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Microglial dysfunction in brain aging and Alzheimer's disease

Abstract: Microglia, the immune cells of the central nervous system, have long been a subject of study in the Alzheimer’s disease (AD) field due to their dramatic responses to the pathophysiology of the disease. With several large-scale genetic studies in the past year implicating microglial molecules in AD, the potential significance of these cells has become more prominent than ever before. As a disease that is tightly linked to aging, it is perhaps not entirely surprising that microglia of the AD brain share some phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
410
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(430 citation statements)
references
References 151 publications
(165 reference statements)
15
410
0
5
Order By: Relevance
“…Converging evidence indicates that the aged brain contains primed and/or senescent microglia (Dilger & Johnson, 2008; Harry, 2013; Mosher & Wyss‐Coray, 2014), which may contribute to age‐related cognitive deficits and altered brain function (Norden et al, 2015). Therefore, we sought to explore the effects of replacing these resident “aged" microglia with new cells, via administration and withdrawal of CSF1R inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Converging evidence indicates that the aged brain contains primed and/or senescent microglia (Dilger & Johnson, 2008; Harry, 2013; Mosher & Wyss‐Coray, 2014), which may contribute to age‐related cognitive deficits and altered brain function (Norden et al, 2015). Therefore, we sought to explore the effects of replacing these resident “aged" microglia with new cells, via administration and withdrawal of CSF1R inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Microglial activation is a hallmark of aging and studies have shown that microglial phenotype and function are altered in the aged brain [reviewed in (Mosher & Wyss‐Coray, 2014)]. To explore how the replacement of aged microglia with new cells affects and shapes the resultant tissue, we employed a method of CSF1R inhibitor‐induced microglial elimination and repopulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been some reports on each glia type in AD pathogenesis, astrocytes, which constitute approximately 30% of cells in the mammalian central nervous system, and oligodendrocytes, are hardly studied in the aging process. Brain aging includes proinflammatory phenotypes, altered signaling, and accumulation of senescent microglia (Harry, 2013; Mosher & Wyss‐Coray, 2014). Abnormalities in microglial cytoplasmic structure were observed in a case study of two nondemented subjects (one 68‐year‐old and one 38‐year‐old) were defined as microglial dystrophy which was further concluded as a sign of microglial cell senescence (Streit, Sammons, Kuhns, & Sparks, 2004).…”
Section: Cellular Changes In Aging and Admentioning
confidence: 99%
“…Initially, microglia respond to and surround plaques, degrading Aβ by phagocytosis (for review, see refs. [6][7][8]. However, chronic activation of these cells shift microglia to a more proinflammatory and less phagocytic state (9,10).…”
mentioning
confidence: 99%